High-order hp-adaptive discontinuous Galerkin finite element methods for compressible fluid flows - Giani, Stefano; Houston, Paul (Springer, 2010)
This article is concerned with the construction of general isotropic and anisotropic adaptive strategies, as well as hp-mesh refinement techniques, in combination with dual-weighted-residual a posteriori error indicators for the discontinuous Galerkin finite element discretization of compressible fluid flow problems.